2019
DOI: 10.3847/1538-4365/ab5364
|View full text |Cite
|
Sign up to set email alerts
|

Abundance Estimates for 16 Elements in 6 Million Stars from LAMOST DR5 Low-Resolution Spectra

Abstract: We present the determination of stellar parameters and individual elemental abundances for 6 million stars from ∼8 million low-resolution (R ∼ 1800) spectra from LAMOST DR5. This is based on a modeling approach that we dub T he Data-Driven P ayne (DD-P ayne), which inherits essential ingredients from both The Payne (Ting et al. 2019) and T he Cannon (Ness et al. 2015). It is a data-driven model that incorporates constraints from theoretical spectral models to ensure the derived abundance estimates are physical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
243
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 198 publications
(263 citation statements)
references
References 96 publications
(117 reference statements)
3
243
0
Order By: Relevance
“…However, the spectral energy distribution (SED) is best fit with an effective temperature of 6000 K. To exclude identification issues, we double checked the identifications of the LAMOST spectrum and the photometry employed for the SED fitting; no misidentifications were detected. In the literature, we also find widely different effective temperature estimates for this star: 5325 K (Ammons et al 2006), 6210 K (Stassun et al 2019), 6785 K (Bai et al 2019), 7950 K (Xiang et al 2019), and 9500 K (Bai et al 2018). The wide range of different temperature values points towards a spectroscopic binary system observed at different phases.…”
Section: Colour-magnitude Diagrammentioning
confidence: 59%
“…However, the spectral energy distribution (SED) is best fit with an effective temperature of 6000 K. To exclude identification issues, we double checked the identifications of the LAMOST spectrum and the photometry employed for the SED fitting; no misidentifications were detected. In the literature, we also find widely different effective temperature estimates for this star: 5325 K (Ammons et al 2006), 6210 K (Stassun et al 2019), 6785 K (Bai et al 2019), 7950 K (Xiang et al 2019), and 9500 K (Bai et al 2018). The wide range of different temperature values points towards a spectroscopic binary system observed at different phases.…”
Section: Colour-magnitude Diagrammentioning
confidence: 59%
“…The first stage of the LAMOST spectroscopic survey [22][23][24][25] was carried out in a low-resolution (R ∼ 2000) mode with a wide spectral wavelength coverage of 3800-9000 Å. Based on abundances from APOGEE DR14 by Ting et al [26], Xiang et al [27] developed a data-driven neural network and derived stellar parameters and [α/Fe] abundances for 8162566 stars from LAMOST DR5. This is an internally consistent dataset (hereafter DDPayne-LAMOST DR5) and thus becomes a good sample for a statistic study.…”
Section: Selection Of Star Samplesmentioning
confidence: 99%
“…assumed single-star spectra. The binarity would be revealed in case of a significant mismatch between the two parallaxes, and this approach is discussed and attempted in Xiang et al (2019). Similarly, Cotar et al (2019) identified objects that are more luminous than predicted by their spectral type and Gaia distance, and specifically focused on double and triple Sun-like stars.…”
Section: Identification Of Binary Starsmentioning
confidence: 99%
“…spectra of solar-type stars. A proper investigation of this effect is therefore essential in order to make the findings of current and future projects dedicated to Galactic archaeology more reliable (see also Xiang et al 2019). To some extent, as indicated in Fig.…”
Section: Undetected Binarity and The Effect On Stellar Parametersmentioning
confidence: 99%
See 1 more Smart Citation